қазақстандық саяси партиялардың имиджі қалыптасуының ерекшеліктері (Journal of Philosophy, Culture and Political Science, 2018)
Characterizing a degree of scientific elaboration of the themes of research, it is important to note, that, despite of a plenty of researches of political image, till the present moment in domestic political science features of formation of image of the Kazakhstan political parties are insufficiently investigated.